Analisis Aktor Kunci Dalam Pengelolaan Air Tanah Dan Air Limbah Di Kota Pekalongan - Shinta Putri; Vita Elysia; Mirza Permana; Shofi Azkarifa (JURNAL LITBANG KOTA PEKALONGAN, 2026)
This study aims to identify the key actors and assess their roles in groundwater utilization and wastewater management in Pekalongan City. It is a qualitative study focused on the perspectives of community groups. Data were collected through snowball interviews involving several stakeholder groups, including local communities, managers of PAMSIMAS wells, business actors, and related associations or community organizations. The data were then analyzed using content analysis and stakeholder analysis. The results show that there are four categories of stakeholders involved in groundwater utilization and industrial wastewater management in Pekalongan City. These categories are government, community (local residents, business actors, and associations/community organizations), the private sector, and academia. Based on the analysis, the main actors in groundwater utilization and wastewater management in Pekalongan City are the government, business actors/PAMSIMAS well managers, and associations/community organizations. This study highlights the importance of cross-sectoral collaboration involving the collective efforts of these actors to support sustainable groundwater utilization and wastewater management in Pekalongan City. The findings can serve as input for the Pekalongan City Government in developing strategies for stakeholder participation to achieve such sustainability.